2002
DOI: 10.1034/j.1600-0897.2002.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Network of Eutopic and Ectopic Endometrium in Women with Adenomyosis

Abstract: The results obtained indicate a significant role of local cytokine production impairment in the development of adenomyosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 16 publications
0
31
0
2
Order By: Relevance
“…Adenomyosis, ectopic endometrium within the myometrium, is characterized by unique patterns of cytokine balance when compared with normal endometrium. 36 Adenomyosis is known to have increased secretions of interferon (IFN)-a, IFN-c, tumor necrosis factor (TNF)-a, and interleukin (IL)-10. 36,37 Increased level of these cytokines may potentially augment the cancer-immune system (IFN-a and IFN-c), anti-tumor effect via enhancing apoptosis (TNF-a), and anti-inflammatory cytokine production (IL-10), resulting in protective effects to endometrial cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenomyosis, ectopic endometrium within the myometrium, is characterized by unique patterns of cytokine balance when compared with normal endometrium. 36 Adenomyosis is known to have increased secretions of interferon (IFN)-a, IFN-c, tumor necrosis factor (TNF)-a, and interleukin (IL)-10. 36,37 Increased level of these cytokines may potentially augment the cancer-immune system (IFN-a and IFN-c), anti-tumor effect via enhancing apoptosis (TNF-a), and anti-inflammatory cytokine production (IL-10), resulting in protective effects to endometrial cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…36 Adenomyosis is known to have increased secretions of interferon (IFN)-a, IFN-c, tumor necrosis factor (TNF)-a, and interleukin (IL)-10. 36,37 Increased level of these cytokines may potentially augment the cancer-immune system (IFN-a and IFN-c), anti-tumor effect via enhancing apoptosis (TNF-a), and anti-inflammatory cytokine production (IL-10), resulting in protective effects to endometrial cancer progression. [38][39][40][41] Adenomyosis is also known to have decreased secretions of various cytokines such as IL-1b, IL-8, and epidermal growth factor (EGF).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (32) reported that abnormal secretion of IL-6 and IL-8 from endometrial stromal cells may have a role in the formation of ectopic islands in adenomyosis. Furthermore, the role of EGF, VEGF and TGF-β implicated in inflammation, angiogenesis and the pathophysiology of endometriosis has been well established (36)(37)(38). Cell invasion is a vital hallmark of tumor formation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In contrast, adenomyosis impairs the function of the myometrium. A recent report showed a significant increase in the myometrial stiffness (estimated with shear wave elastography) in patients with adenomyosis.…”
mentioning
confidence: 99%